Dietary protein-phenolic interactions: characterization, biochemical-physiological consequences, and potential food applications - Zhang, Qiaozhi; Cheng, Zhouzhou; Wang, Yanbo; Fu, Linglin (Critical reviews in food science and nutrition, 2021)
Dietary proteins and phenolic compounds are commonly co-existing components that readily interact with each other to yield complexes in a wide range of food systems. The formed complexes play a critical role in the physiochemical characteristics of both reacting molecules, thereby impacting nutritional and quality profiles of related products. In this review, we provided the most updated knowledge on dietary protein-phenolic interactions related with food science and human nutrition, including their mechanisms of complexation, analytical technologies, and alterations in the functionality and nutraceutical properties of both reacting partners. Their potential applications in the industries regarding stability during food processing and storage, impacts on product quality, and fabrication of novel delivery systems for liable bioactives were also discussed. The interactions between dietary proteins and phenolics, either via non-covalent or covalent processes, are ubiquitous in food systems and are closely associated with chemical structures of both compounds and the surrounding conditions, mainly temperature, pH, and the presence of phenolic oxidases. Albeit in different ways, such intermolecular associations induced changes in protein conformational structures, which subsequently impacted their techno-functional properties, digestibility, and allergenic potentials; in turn, the bioaccessibility/bioavailability and health-protecting features of interacted phenolics were modified to various extents, as noticed by in vitro and in vivo evidence. Largely depending on the interaction molecules and preparation steps, those influences can be either favorable or unfavorable in different systems and therefore can be tailored to develop food products and nutraceuticals with maximized functionality and quality attributes.